A Psychological Perspective of Stand-up Comedians in the Construction of Political Humor - Singgih Adi Nur Wikandaru; Dessy Nurfajar Jasmine Tamnge; Evie Prihanti Muliasari; Rilla Sovitriana (Siber Nusantara of Education and Sport Review, 2026)
This study aims to explore the construction of political humor in stand-up comedy from the psychological perspective of comedians. This research employed a descriptive qualitative approach involving three comedians as participants selected through purposive sampling. Data was collected through semi-structured interviews and analyzed using thematic analysis. The findings show that political humor is constructed through the transformation of personal and social concerns into material that can be accepted by the audience. This process involves consideration of the audience, risk perception, and social norms, and is influenced by social factors such as community support and audience responses. These findings indicate that political humor is a form of benign violation constructed through the interaction between individual and social factors and contributes to expanding the study of humor psychology by highlighting humor as a construction process from the creator’s perspective.